Acute Anterior Reinfarction Complicating with Transient Symptomatic Total Atrioventricular Block - Hendiperdana, Mochamad Rizky; Firdaus, Isman (The Indonesian Heart Association, 2022)
Background Acute stent thrombosis is a frequent cause of myocardial infarct (MI) after stent placement. Total atrioventricular (AV) block is frequently become the conductive disturbance complication of acute reinfarct. Inferior MI has Low long-term mortality and greater reversibility than anterior MI which has higher in-hospital and long-term mortality. Case Illustration A 44-year-old man, came to emergency department Cardiovascular Centre Harapan Kita with altered mental status since 12 hours ago. PPCI stenting at proximal LAD of his acute anterior MI 2 days ago. Patient had acute stent thrombosis then underwent urgent PCI at referring hospital. Patient present with blood pressure 57/30, heart rate 20 -30 with TAVB rhythm. Laboratory showed increased serum lactate level 5.2. Patient was diagnosed with Total AV block caused by MI. Patient was planned for emergency temporary pacemaker (TPM) implantation. After 24 hours close monitoring, the patient intrinsic rhythm resolved with spontaneous recovery. Patient was hemodynamically stable until discharge. Discussion Stent thrombosis of proximal stent of LAD will cause TAVB because of the source of the distal portion of the AV node is originating from septal branch of LAD. It is caused by extensive necrosis with higher in-hospital and long-term mortality, often culminated in permanent pacemaker. However, spontaneous recovery of TAVB into sinus rhythm take place. This could be caused by transient reversible ischemia of infra nodal region of AV node which supplied by septal perforator branch Conclusion This case reporting a complete atrioventricular block during the course of acute anterior reinfarct and had spontaneous resolution of the AV block. Mechanisms of spontaneous resolution of complete AV block in the setting of acute MI is associated transient ischemia after occlusion of proximal LAD.This article has a related Erratum.